PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN WORD OF MOUTH”(STUDI KASUS PROGRAM LANJUTAN DI SBU LP3I GROUP)” PERIODE 2013-2014 - Istna Fibriyadi (POLITEKNIK LP3I JAKARTA, 2016)
The Influence of the quality of service for satisfaction and word of mouth on the further education LP3I Campus Kramat Jakarta. Research is aimed to determine the influence of the quality of service for satisfaction student an continued program LP3I, know the influence of the quality of service for word of mouth students an continued program LP3I, and he knows influence of satisfaction with word of mouth students an continued program LP3I. Data processing the result of this research in a software partial least square (pls) does not need sample in a specified number of, but the amount available recommended was a minimum 35 to 100 respondents (yamit and kurniawan, 2009:213). Each respondent given 59 statement with use likert scale. Based on the results of data processing shows that the quality of service have leverage significant and give a positive response to satisfaction on program LP3I secondary schools. The quality of service have leverage significant and give a positive response to the word of mouth on schooling LP3I an continued program. And satisfaction have leverage significant and give a positive response to the word of mouth on schooling LP3I an continued program.Keywords:the quality of services , satisfaction , word of mouth